The Impact of GDP per Capita, Intergovernmental Transfers, and Labor Force on Regional Financial Independence in East Java, Indonesia: A Panel Data Analysis (2014–2023) - Ulah, Nur Azizah Afifatul (University Merdeka Malang, 2025)
This study investigates the determinants of regional financial independence in East Java, Indonesia, focusing on the influence of Gross Regional Domestic Product (GRDP) per capita, intergovernmental transfers, and the working population over the period 2014–2023. Using a panel data regression model with a fixed-effects approach, we analyze data from 38 regencies/cities, sourced from the Central Bureau of Statistics, the Indonesian Ministry of Finance, and the Directorate General of Fiscal Balance. Results reveal that GRDP per capita and the working population significantly enhance financial independence, while intergovernmental transfers exhibit a negative impact. Specifically, a 1% increase in GRDP per capita elevates financial independence by 1.34%, and a 1% rise in the working population contributes 1.56% to independence. Conversely, transfers to regions, though intended to support decentralization, reduce independence by 1.89% for every 1% increase, reflecting over-reliance on central government funding. The adjusted R-squared value of 93% indicates robust explanatory power of the model.These findings underscore the critical role of local economic productivity and labor market participation in fostering fiscal autonomy, while highlighting the need for strategic reallocation of transfer funds to stimulate local revenue generation. The study concludes that policies prioritizing investment in high-productivity sectors and job creation are essential to reduce dependency on central transfers and strengthen regional financial resilience.